Evaluation of Planning and Preparation Stages on Health Functional Position Comptency Test in Banyumas Regency 2020 - Bonisa Nursari; Arih Diyaning Intiasari; Yuditha Nindya Kartika Rizqi (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2021)
Background: On 2020, Health Functional Position Competency Test in Banyumas Regency has been rescheduled repeatedly and just happened in November. This makes difficulty on health workers promotion process, because the health workers who will increase their functional position level don't have competency certificate yet. This study aims to evaluate planning and preparation stages on Health Functional Position Competency Test in Banyumas Regency 2020. Methods: This study is a qualitative research with case study design and located in Banyumas Regency with the number of informants as many as 9 people. The informant consists of main informant and supporting informant. Data analysis used content analysis with thematic network approach. Results: Evaluation of planning and preparation stages on Health Functional Position Competency Test explained that the available resources are not fully ready for doing implementation process. The available of human resources don't have a good understanding about technical process in planning and preparation stages. This happened because the guidelines that have been used not explain clearly about technical implementation of Health Functional Position Competency Test. So, it is needed to create SOP and increase socialization activity, so the availability of human resources like organizer team, examiner team and health workers from UPTD/Hospital understand detail information about technical implementation of Health Functional Position Competency Test. Conclusion: In 2020, rescheduling of Health Functional Position Competency Test happened because the turnover of some employees occurred and it's not supported by the availability of SOP as a technical guideline. In addition, COVID-19 pandemic also affected the situation due to limited face to face activity.